2020
DOI: 10.1111/jch.13979
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between high‐normal albuminuria and arterial stiffness in Chinese population

Abstract: Microalbuminuria, a hazard factor of cardiovascular events in hypertensives, diabetics, and general population, 1-3 is defined as urinary albumin-to-creatinine ratio (UACR) between 30 and 300 mg/g. 4 It is generally believed that microalbuminuria is not only an indicator of glomerular endothelial damage representing microvascular injuries, but also reflects widespread vascular damage. 5 Actually, endothelial injury occurs at the same time in both large and small arteries. Arterial wall consists of endothelium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
(50 reference statements)
2
18
0
1
Order By: Relevance
“…High blood pressure is a crucial risk factor of arterial stiffness and associated with cardiovascular mortality. Current study has showed a strongly correlation between BP and cfPWV in both males and females, which is consistent with previous studies 4,34 . Our previous studies have reported that BP is one of important risk factor of cfPWV, and the presence of hypertension played the most important role in progress of arterial stiffening even compare with age 4,34 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High blood pressure is a crucial risk factor of arterial stiffness and associated with cardiovascular mortality. Current study has showed a strongly correlation between BP and cfPWV in both males and females, which is consistent with previous studies 4,34 . Our previous studies have reported that BP is one of important risk factor of cfPWV, and the presence of hypertension played the most important role in progress of arterial stiffening even compare with age 4,34 .…”
Section: Discussionsupporting
confidence: 92%
“…Current study has showed a strongly correlation between BP and cfPWV in both males and females, which is consistent with previous studies. 4,34 Our previous studies have reported that BP is one of important risk factor of cfPWV, and the presence of hypertension played the most important role in progress of arterial stiffening even compare with age. 4,34 However, some scholars have demonstrated that arterial stiffening predicts the progression of BP and development of hypertension but not the consequence recently.…”
Section: F I G U R Ementioning
confidence: 99%
“…The methods have been described before. 14 , 15 , 16 , 17 , 18 , 19 Briefly, serum creatinine levels were measured using an enzymatic method. 14 , 15 , 16 , 17 , 18 , 19 Serum uric acid, total cholesterol, triglycerides, high‐density lipoprotein (HDL) cholesterol, and low‐density lipoprotein (LDL) cholesterol levels were analyzed via the oxidase method.…”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 , 18 , 19 Briefly, serum creatinine levels were measured using an enzymatic method. 14 , 15 , 16 , 17 , 18 , 19 Serum uric acid, total cholesterol, triglycerides, high‐density lipoprotein (HDL) cholesterol, and low‐density lipoprotein (LDL) cholesterol levels were analyzed via the oxidase method. 14 , 15 , 16 , 17 , 18 , 19 The estimated glomerular filtration rate (eGFR) was assessed by the modification of diet in renal disease (MDRD) formula: eGFR [mL / (min·1.73 m 2 )] = 186 × [serum creatinine (mmol/L) ×0.0113] –1.154 × (Age) –0.203 , and adjustments for gender were 1 for male and 0.742 for female.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation